Correlation Between Limb Length and Muscle Mass of The Lower Extremity - Firmansyah, Awang; Tjahyaningtijas, Hapsari Peni Agustin; Rasy, Ahmad Hafizh Ainur; Budijono, Agung Prijo; Putro, Andika Bayu; Putra, I Wayan Valentino Eka (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2024)
Introduction: Muscle mass has a contribution to body strength. One third of the human body is part of the lower extremity. The limbs are part of the lower extremity. This study aims to investigate the length of the limb with muscle mass. Methods: Cross-sectional study with the subjects of this study were 39 students (12 females and 27 males) with male characteristics (age 20.03±0.7, height 168±5.46, weight 61.92±10.98, BMI 22±4.24) while in women (age 20.16±0.83, height 158.83.3±5.13, weight 54.7±12.02, BMI 21.65±4.51). Pearson correlation from SPSS version 26 with a significance level of P-value < 0.05. Findings: Based on the data, there was a signifi correlation between the length of the leg and muscle mass on both the right (P-value: 0.000, r: 0.634) and the left (P-value: 0.000, r: 0.629). Conclusion: This study proves that the longer the limbs a person has, the greater the muscle mass he has.